Increasing library intelligence by harmonizing assessment tools - Giannopoulou, Aggeliki; Giannopoulou, Georgia; Goudis, Alexandra; Tsakonas, Giannis (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2019)
Academic libraries are considered as key factors in the educational system of a country and strong pylons for the economic development and societal cohesion. Libraries have always intended to provide qualitative services and frequently run surveys that measure the opinion of their users. Our contribution aims to show how the findings of a survey can be aligned with information from other assessment tools to better inform library management. We analyze external data of our Library’s performance as collected by an electronically conducted survey in May 2018. The initial objective was to collect 1000 questionnaires from all registered Library users; however, 950 questionnaires were collected in a two weeks’ period, securing the quota sampling conditions. Descriptive statistical analysis via SPSS was conducted to find the key measurements and to explore deeper the various associations. At the same time, we compared the scores of library performance as reflected in internal managerial assessment practices over the span of two years. This study follows an approach that exploits the existing percentage measurement scale for the assessment of Greek public sector employees to gather users’ opinion on certain performance categories. This scale, as well as its interpretation module, is used for the harmonization of the information that comes from varied assessment notions, tools and practices. Our survey findings showed that the library users were well satisfied with the conduct of staff and think that the library has margins for improvement to fulfill its role as a study place and collection. These findings seem close to the respective internal assessment scores. Therefore, our study showcases that there can be a harmonization of various assessments tools, internal and external, and the library administration can be informed about its performance in a coherent way.